Sucrose regulated expression of a Ca2+-dependent protein kinase (TaCDPK1) gene in excised leaves of wheat - Martínez Noël, Giselle María Astrid (2007)
Sucrose (Suc) can influence the expression of a large number of genes and thereby regulates many metabolic and developmental processes. However, the Suc sensing and the components of the ensuing signaling transduction pathway leading to the regulation of gene expression are not fully understood. We have shown that protein kinases and phosphatases are involved in the Suc induced expression of fructosyltransferase (FT) genes and fructan accumulation by an hexokinase independent pathway in wheat (Triticum aestivum). In the present study, using an RT-PCR based strategy, we have cloned a calcium-dependent protein kinase (TaCDPK1) cDNA that is upregulated during Suc treatment of excised wheat leaves. The deduced amino-acid sequence of CDPK1 has high sequence similarity (>70%) to known CDPKs from both monocots and dicots. Based on sequence homology, TaCDPK1 sequence shows a variable domain preceding a catalytic domain, an autoinhibitory function domain, and a C-terminal calmodulin-domain containing 4 EF-hand calcium-binding motifs, along with a N-myristoylation motif in the N-terminal variable domain. The recombinant Escherichia coli expressed TaCDPK1 was able to phosphorylate histone III-S in a calcium dependent manner in in vitro assays. The TaCDPK1 gene expression, as determined by quantitative RT-PCR, is induced by Suc and this effect is repressed by the inhibitors of the putative components of the Suc signal transduction pathway (calcium, Ser/Thr protein kinases and protein phosphatases). We propose that TaCDPK1 is involved in the Suc induced signaling pathway in wheat leaves.